Preparation method of bubble mud for improvement of earth pressure balance shield earth - HU JIANNAN; WANG LU; ZHU WEI; QIAN YONGJIN; XU CHAO; WANG CHAO (2019)
The invention discloses a preparation method of bubble mud for improvement of earth pressure balance shield earth. The preparation method comprises following steps: firstly, preparing basic mud; uniformly mixing and stirring a foaming solution and mud; generating the bubble mud; placing the basic mud in a closed or semi-closed container, and stirring the basic mud by a stirrer to obtain the bubblemud. The bubble mud prepared with the method has good economic efficiency and stability, has properties of improving liquidity, adjusting strength and reducing permeability coefficient like bentonitemud, is suitable for earth improvement of an earth pressure shield machine, effectively reduces torque and improves fluidity and anti-permeability of the earth. 本发明公开了种用于土压平衡盾构舱土改良的气泡泥浆制备方法，包括以下步骤：首先配置基浆：将发泡液和泥浆混合搅拌均匀；然后生成气泡泥浆：将基浆放置在密闭或半密闭容器中，用搅拌器搅拌基浆，得到气泡泥浆。采用本发明提供的方法制备得到的气泡泥浆经济性、稳定性好，类似于膨润土泥浆、具有改善流动性、调节强度、降低渗透系数的性能，适用于土压盾构机的舱土改良，有效降低扭矩、提高舱土的流动性和抗渗性。